Hierarchically Assembling CoFe Prussian Blue Analogue Nanocubes on CoP Nanosheets as Highly Efficient Electrocatalysts for Overall Water Splitting. Issue 7 (28th May 2021) - Quan, Li; Li, Shuohan; Zhao, Zhanpeng; Liu, Jianqiao; Ran, Yue; Cui, Jiayi; Lin, Wei; Yu, Xuelian; Wang, Lin; Zhang, Yihe; Ye, Jinhua
Abstract: Efficient and durable electrocatalysts are highly desirable for overall water splitting. Herein, a facile strategy is demonstrated to rationally construct CoFe Prussian blue analogues (PBA)@CoP cube‐on‐sheet hierarchical structure by etching reaction with intermediated CoO to form PBA nanocubes. Benefitting from the heterostructured engineering, the as‐synthesized CoFe PBA@CoP presents remarkable electrocatalytic performance in 1.0 m KOH, only requiring overpotentials of 100 mV for hydrogen evolution reaction (HER) and 171 mV for oxygen evolution reaction (OER) to reach the 10 mA cm −2 current density with good stability. Extraordinarily enhanced electrocatalytic performance is ascribed to not only the rapid charge transfer of active species, but also the synergistic effect between each component to achieve tuned electronic structure and abundant electrocatalytic active sites. Especially, the assembled two‐electrode cell using CoFe PBA@CoP as both cathode and anode delivers the current densities of 10 mA cm −2 at a relatively low cell voltage of 1.542 V, outperforming most of low‐cost bifunctional electrocatalysts reported to date. The controllable and versatile strategy will open up an avenue to prepare hybrid films for advanced electrochemical energy storage and conversion. Abstract : An in situ sacrificial strategy is established to construct CoFe PBA@CoP cube‐on‐sheet architectures. Benefitting from the advantage of rich active sites, shortened electron and ion pathways, and greatly improved structural stability from the synergistic modulation of geometric and electronic structure, the CoFe PBA@CoP presents remarkable bifunctional electrocatalytic activity and stability in the overall water splitting reaction in alkaline solution.